PENGARUH MOTIVASI, PELATIHAN DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI - Leonard Rumadas; Yulius Heri Saptomo; Louis S. Bopeng (Cakrawala Management Business Journal, 2022)
ABSTRACT The aim of this research is to knows determine motivation, training and work facilities have a partial and simultaneous effect on the performance of employees of the Personnel and Human Resources Development Agency. In carrying out this research, the type of research used is quantitative research. The sample determination technique uses a saturated sample, that is, all members of the population are sampled. The data collection techniques used are observation, interviews and questionnaires. For instrument testing using validity and reliability tests. Whereas the data analysis technique uses Multiple Regression formulated in the equation Y= α + β1X1 + β2X2 + β3X3 + e. The results showed that Motivation does not have a significant effect on employee performance, Training has a significant effect on employee performance, work facilities do not have a significant effect on employee performance, Motivation, training and work facilities simultaneously affect employee performance.